ANALISIS EFISIENSI PEMAKAINAN BAHAN BAKAR MESIN INDUK KAPAL PURSE SEINER DI PELABUHAN PENDARATAN NUSANTARA PEKALONGAN - Sa’id, Solichin Djazuli (Gema Teknologi, 2011)
Solichin Djazuli Sa’id, in this paper explain that fuel consumption for each vessel were variations depending on the size of ships, ships with a larger size will require more fuel for each mile distance the ship with  a GT 101 for a distance of 1 mile with a speed of 6 knots require diesel fuel (dieselfue oil ) 6.24 liter, GT 1991: 6.06 liter, GT 80: 5.69 liter, GT 71: 5.13 liter, GT 61;4.74 liter and most economical is the GT 45 is only 3.30 liters per milnyaThe lowest operating costs of fishing vessels is to measure 45GT, 101GT highest. Operational Cost (OC) is the most economical ship with size 45 GT (Modern I).Operational costs are dominating the supply of fuel (diesel) 44%.Profit rate (profit rate) obtained by vessels of 45 GT (Modern I)  has a rate of returnabove 15%, the highest in comparison  with vessels of above. Keywords: Fuel consumption, operating costs